Rotation and Magnetic Force Effects on Peristaltic Transport of Non -Newtonian Fluid in a Symmetric Channel - Amaal Mohi Nassief ,; M.Abdulhadi, Ahmed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In this paper, the impact of magnetic force, rotation, and nonlinear heat radiation on the peristaltic flow of a hybrid bio -nanofluids through a symmetric channel are investigated. Under the assumption of a low Reynolds number and a long wavelength, the exact solution of the expression for stream function, velocity, heat transfer coefficient, induced magnetic field, magnetic force, and temperature are obtained by using the Adomian decomposition method. The findings show that the magnetic force contours improve when the magnitude of the Hartmann number M is high and decreases when rotation increases. Lastly, the effects of essential parameters that appear in the problem are analyzed through a graph. Plotting all figures is done using the MATHEMATICA  software.